2019
DOI: 10.1111/rsp3.12197
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency estimation and its role in policy recommendations: An application to the Kenyan livestock sector

Abstract: Livestock represents 12% of Kenya's economy, and an increase in its efficiency can improve development and reduce poverty. A parametric stochastic frontier model was fitted to a large farm-level cross-sectional data set to estimate the efficiency levels and the underlying sources of the output's departure from the optimal levels. We found that the overall mean efficiency in most of the production frontier models is fairly high (above 51%) and sensitive to the model choice. The main factors that significantly r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 32 publications
1
8
0
Order By: Relevance
“…To date, the SFA has become the framework of choice of many scholars (e.g. Coelli [1995], Jondrow et al [1982], Kumbhakar-Tsionas-Sipiläinen [2009], Schmidt [2011], Mamardashvili-Bokusheva [2014], Baráth-Fertő [2015], Martinez et al [2016], Bahta et al [2018], Manyeki-Kotosz [2019]) in the estimation of TE levels for economic agents.…”
Section: Parametric Stochastic Fpfmentioning
confidence: 99%
“…To date, the SFA has become the framework of choice of many scholars (e.g. Coelli [1995], Jondrow et al [1982], Kumbhakar-Tsionas-Sipiläinen [2009], Schmidt [2011], Mamardashvili-Bokusheva [2014], Baráth-Fertő [2015], Martinez et al [2016], Bahta et al [2018], Manyeki-Kotosz [2019]) in the estimation of TE levels for economic agents.…”
Section: Parametric Stochastic Fpfmentioning
confidence: 99%
“…Following these observations, it is expected that livestock farming households who have access to veterinary services have health sound animals and also widens the household's knowledge concerning the use of improved livestock production technologies and this is likely to influence market participation decision of a household positively. Additional, veterinary services and advisory services (either through extension or agricultural research) as observed in Manyeki-Kotosz (2019) study may lead to more technical inefficiency.…”
Section: Procedures For Estimation Market Participation Modelmentioning
confidence: 90%
“…This study follows Rakipova et al (2003) approach and the dependent variable Y stand for tropical livestock unit (TLU) 26 and comprises of cattle representing large ruminant, and sheep and goat representing small-stock ruminate. A similar approach was also applied in the study by Lekunze-Luvhengo (2016) and Manyeki-Kotosz (2019) where the number of livestock produced per year were converted to TLUs which is equivalent to physical weights approach applied in Rakipova et al (2003) study. Different livestock species were combined into one herd, and this was necessitated because, under pastoral set-up, the three species (i.e.…”
Section: Contextual Variablesmentioning
confidence: 99%
See 2 more Smart Citations